FORMALIZATION OF MARKETING AND FINANCE MANAGEMENT INTERFACE - Leitoniene, Sviesa; Sapkauskiene, Alfreda; Kloviene, Lina (European Scientific Journal, ESJ, 2013)
Actually, in the theory of company’s finance management and marketing is more often acknowledged that marketing activity create company’s financial value, however in practice it is complicated to valuate the contribution of marketing in creating firm value and substantiate marketing investments in the viewpoint of value based management. In this article attempts are made to formalize the impact of marketing/finances management systems interface for firm value. The scientific problem handled in the article is defined as following: formalization of marketing/finance management systems interface impact to the firm value. The purpose is using mathematical logic carry out comparative analysis of theoretical models as well as empirical investigations, analyzing interface of marketing and finance management from the viewpoint of firm value. Theoretical interpretation of marketing/finance management systems interface as well as its effect for firm value has been presented, basing on which the main contact points of marketing and finance management systems are highlighted. Two dominant business objectives: establishing competitive advantage and creating shareholder value, are not conflicting rather equivalent objectives originating from a single economic framework. Comparative analysis of models investigating the effect of marketing decisions to firm value has been performed it singled out the relationship between marketbased assets and cash flow as the main connecting-link in creation of marketing decisions and firm value.